Rural‐Urban Differences in Perceptions of Child Overweight Among Children and Adolescents, Their Guardians and Health Care Professionals in the United States. Issue 1 (12th August 2015) - Tarasenko, Yelena N.; Chen, Chen; Smalley, K. Bryant; Warren, Jacob
Abstract: Research Objective: Children and adolescents residing in rural environments with higher prevalence of an overweight population may develop inaccurate perceptions of a healthy weight. This study examines rural‐urban differences in perceptions of child overweight among overweight (85 ≤ BMI percentile < 95) and obese children (BMI percentile ≥ 95), their guardians and health care providers (HCPs), and children's concomitant weight control. Methods: The cross‐sectional study was based on the 2005‐2010 NHANES data (1, 844 overweight and obese children and adolescents, aged 8‐15 years). Rurality was defined using the 2003 RUCC. The weight status was based on the standardized measures of children's height and weight. Children reported whether they considered themselves overweight and whether they were trying to lose weight. Proxy respondents (ie, guardians) reported whether they considered their child to be overweight and whether an HCP had ever told them their child was overweight. Weighted percentages and predicted probabilities from multivariable logistic regressions were calculated, accounting for the complex, multistage, probability sampling design and nonresponse. Findings: Rural residents comprised 18.8% of the study population; 41.8% of them were overweight and 58.2% were obese compared to 46.7% and 53.3% of urban peers, respectively. Misperceptions of children's weight status were 11.3 and 6.0 percentage points higher in rural children and their guardians, respectively. Recall of an HCP identification of child overweight was 6.3 percentage points lower among rural versus urban guardians. Conclusion: Obesity prevention efforts may be fostered by improving accuracy of child overweight perceptions. This may be particularly impactful in rural settings, where weight misperceptions are high.